Mental health as a prerequisite for functioning as optimally as possible in old age: A phenomenological approach - Samal Al Gilani; Lina Tingö; Annica Kihlgren; Agneta Schröder (Wiley, 2021)
Abstract Aim To describe the impact of mental health on the ability to function optimally among older adults experiencing mental health issues. Design This study had a descriptive qualitative design. Methods Six older females with a Hospital Anxiety and Depression Scale (HADS) score of ≥8 on either of the subscales (depression or anxiety) participated in individual interviews. All data were analysed using a phenomenological approach influenced by Giorgi. Results The phenomenological analysis led to a structured synthesis comprising the following three themes: (a) life situations affecting mental health, (b) consequences of mental health in everyday life and (c) strategies for maintaining mental health.